Incidence of Seizure and Associated Risk Factors in Patients in the Medical Intensive Care Unit (ICU) at Memorial Sloan Kettering Cancer Center (MSK) from 2016–2017. (October 2022) - Azary, Saeedeh; Caravanos, Christopher; Reiner, Anne S.; Panageas, Katherine S.; Dhawan, Vikram; Avila, Edward K.
Background: Seizures and status epilepticus are common neurologic complications in the intensive care unit (ICU) but the incidence in a cancer ICU is unknown. It is important to understand seizure risk factors in cancer patients to properly diagnose the seizure type to ensure appropriate therapy.Methods: We identified patients admitted to the medical ICU at Memorial Sloan Kettering Cancer Center (MSK) from January 2016 to December 2017 who had continuous or routine electroencephalography (EEG) and identified clinical and electrographic seizures by chart review.Results: Of the 1059 patients admitted to the ICU between 2016 and 2017, 50 patients had clinical and/or electrographic seizures (incidence of 4.7%, 95% CI: 3.4-6.0). The incidences of clinical and electrographic seizure were 4.1% and 1.1%, respectively. In a multivariable stepwise regression model, history of seizure (OR: 2.9, 95% CI: 1.1-7.8, P : .03), brain metastasis (OR: 2.5, 95% CI: 1.1-5.8, P: .03), vasopressor requirement (OR: 2.2, 95% CI: 1.0-4.9, P : .05), and age < 65 (2.4, 95% CI: 1.2-5.0, P : .02) were associated with increased risk of seizure (either clinical or electrographic). Obtaining continuous EEG instead of routine EEG increased the yield of seizure detection significantly (OR: 3.9, 95% CI: 1.3-11.1, P : .01). No chemotherapy in the past 30 days, no antibiotic use, vasopressor requirement, and having a brain tumor increased risk of electrographic seizure. Length of continuous EEG > 24 h significantly increased the chances of both clinical and electrographic seizure detection, (OR: 2.6 [95% CI: 1.2-5.7] and 15.0 [95% CI: 2.7-82.5], respectively).Conclusions: We identified known and cancer-related risk factors which can aid clinicians in diagnosing seizures in cancer ICUs. Long-term video EEG monitoring should be considered, particularly given the treatable and reversible nature of seizures.